2022
DOI: 10.1101/2022.03.15.484434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust group- but limited individual-level (longitudinal) reliability and insights into cross-phases response prediction of conditioned fear

Abstract: Here we follow the call to target measurement reliability as a key prerequisite for individual-level predictions in translational neuroscience by investigating i) longitudinal reliability at the individual and ii) group level, iii) cross-sectional reliability and iv) response predictability across experimental phases. 120 individuals performed a fear conditioning paradigm twice six month apart. Analyses of skin conductance responses, fear ratings and BOLD-fMRI with different data transformations and included n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…Taken together, this means that it is currently unclear to what extent our results reflect stable individual traits, as opposed to participants’ particular states at the time of measurement, which limits the interpretation of our findings. In line with Klingelhöfer-Jens et al, 2022 (Preprint) we encourage future research on individual differences in fear conditioning to explore new ways of improving the reliability of measurement.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Taken together, this means that it is currently unclear to what extent our results reflect stable individual traits, as opposed to participants’ particular states at the time of measurement, which limits the interpretation of our findings. In line with Klingelhöfer-Jens et al, 2022 (Preprint) we encourage future research on individual differences in fear conditioning to explore new ways of improving the reliability of measurement.…”
Section: Discussionmentioning
confidence: 83%
“…In summary, while the use of a twin sample is a limitation of the present study, we contend that there is no reason to conclude that it invalidates the reported results. Finally, it should be noted that only a few studies to date have examined the longitudinal (test-retest) reliability of individual differences in discriminatory fear learning measured by SCR ( Cooper et al, 2022 , Preprint; Klingelhöfer-Jens et al, 2022 , Preprint). While one study found evidence of fair within-person stability in 51 participants across a 9-day period ( Cooper et al, 2022 , Preprint), another study found evidence of poor individual-level reliability in 120 participants across a 6-month period ( Klingelhöfer-Jens et al, 2022 , Preprint).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…triallevel variance), and n is the number of trials. In practice, this relationship often holds [7,8] though with some exceptions [41,42]. Notably, increasing the number of task trials only benefits reliability if measurement error is random.…”
Section: Decreasing Measurement Noise 321 Increasing Trial Numbersmentioning
confidence: 99%